The origins of the denominative type Lith. ‑áuti, ‑áuja, OCS ‑ovati, ‑ujǫ - Villanueva Svensson, Miguel (Baltistica, 2014)
The article deals with the origin of the denominative suffix Lith. ‑áuti, ‑áuja, OCS ‑ovati, ‑ujǫ and offers a completely new theory.